Pengaruh Total Aset Dan Dana Pihak Ketiga (DPK) Terhadap Pembiayaan Bank Bukopin Syariah Periode Tahun 2018-2022 - Panji Rahmansyah; M. Ruslianor Malika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
A bank's funding, DPK, and total assets can all be used to gauge its success. The bank's total assets and DPK have an impact on how much funding it offers to the general population. The aim of this study is to apply quantitative descriptive approaches to uncover cause-and-effect correlations in the relationship between Total Assets, Third Party Funds, and Financing at Bank Bukopin Syariah from 2018 to 2022. The data utilised comes from the audited financial reports for the years 2018 through 2022 of Bank Bukopin Syariah, which can be accessed on the bank's official website. Multiple linear regression and conventional assumptions were used in the study to evaluate the hypotheses. Financing (Y), Third Party Funds (X2), and Total Assets (X1) were the variables in the analysis. The statistical t test analysis utilising SPSS output at a significance threshold of 0.05 finds a significant result of 0.002 <0.05, suggesting that Total Assets has a partial effect on Financing. Conversely, Third Party Funds do not appear to have any effect on funding, as shown by their larger-than-0.05 significant value of 0.134. The F test analysis's findings show a significant value of 0.006 < 0.05, which suggests that financing from total assets and third party funds is significantly influenced. Keywords: Total Assets, Third Party Funds (TPF), Financing.